Hydrogenation of carbon dioxide to Formate using a cadmium-based metal–organic framework impregnated with nanoparticles - Makuve, Nyasha; Darkwa, James; Mehlana, Gift; Makhubela, Banothile C. E. (MDPI, 2022)
The burning of fossil fuels to meet energy demands has increased carbon dioxide (CO2) in the atmosphere, causing global warming and associated climate change. Therefore, new materials are being developed to capture CO2 effectively, limit its impact on the environment, and store and/or utilise it as an abundant C1 building block. In this study, we investigate a cadmium(II) metal–organic framework, [Cd(bdc)(DMF)]n (MOF1), synthesised by treating benzene-1,4-dicarboxylic acid with four equivalents of [Cd(NO3)2]. MOF1 was then used to support Pd, Ni, and Pt nanoparticles in forming MOF1/Pd MOF1/Ni and MOF1/Pt, respectively. These MOF-based materials were characterised using powder X-ray diffraction (PXRD), Fourier-transform infrared (FTIR), energydispersive X-ray spectroscopy (EDX), selected area electron diffraction (SAED), and high-resolution transmission electron microscopy (HR-TEM). MOF1/Pd MOF1/Ni and MOF1/Pt proved highly active in the catalytic hydrogenation of CO2 to formate selectively; in contrast, MOF1 did not hydrogenate CO2 to formate. The MOF1/Pd, MOF1/Ni, and MOF1/Pt catalysts produced formate selectively, with the highest TON of 1500 (TOF of 69 h􀀀1) achieved using MOF1/Pd as the catalyst at 170 C within 2 h. A formate yield of 98% was obtained, which demonstrates that the combination of nanoparticles and MOFs greatly enhances the catalytic activity of the active sites.